2022
DOI: 10.37077/25200860.2022.35.1.10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Food Additives on Growth Parameters of Grass Carp Ctenopharyngodon idella Fingerlings

Abstract: A laboratory experiment was carried out to investigate the effect of Thepax and Endo Vit. C as feed additives in the formulated diet on the growth performance of grass carp Ctenopharyngodon idella. The feed (30.11% crude protein) manufactured in the laboratory using raw local materials diet. Young grass carp (Average weight 3.36± 0.95 g) obtained from Aquaculture Unit ponds in Al-Hartha Station for Agricultural Researches, North Basrah. The fish were stocked in nine glass aquarium, three replicates for each tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Al-Faragi 23 also increased weight indicator values by adding the prebiotic beta-glucan to common carp feed for eight weeks. While the results of the present study did not agree with those of Taher et al 24 in grass carp (Ctenopharyngodon Idella) when adding 1 g/kg Thepax and 1 g/kg vitamin C to the diets, as no statistically significant differences were recorded with the control treatment in final weight and weight gain.…”
Section: Discussioncontrasting
confidence: 99%
“…Al-Faragi 23 also increased weight indicator values by adding the prebiotic beta-glucan to common carp feed for eight weeks. While the results of the present study did not agree with those of Taher et al 24 in grass carp (Ctenopharyngodon Idella) when adding 1 g/kg Thepax and 1 g/kg vitamin C to the diets, as no statistically significant differences were recorded with the control treatment in final weight and weight gain.…”
Section: Discussioncontrasting
confidence: 99%
“…Nutrition is an important factor effects on the growth and physiological performance of fish [4]. This composition depends on feed industry according to scientific study, calculates the proportions of its components mainly from protein to energy and other nutrients [7]. The cost of diet for fish farm projects is estimated at 70-76% of the total cost, Therefore, it is necessary to reach the most appropriate diet that provides sufficient need without wasting nutrition resources [5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of floating feed technology can save it from loss, which was made according to modern technologies, therefore, the feed material does not dissolve in the water and remains floating for a long time, which leads to no change in the quality and color of the water or loss in the nutrients from the feed or the active substances that have a positive effect on the growth of fish [6]. Quantity of feed provided depending on the weight of the biomass, The type of fish determines the type of feed provided, as the available natural food contributes to raising floating cages in rivers or lakes by supporting growth in a simple way, The percentage of feeding used for the floating cage system is 3-7% of the weight of the biomass and research and experiment confirmed that the ideal percentage is 5% of biomass weight of floating feed [7]. In Recent Years, the improvement of fish projects, has led to a development of many new diets to promote fish growth and support health [8].…”
Section: Introductionmentioning
confidence: 99%
“…There were many local studies on grass carp. Taher et al (2022) studied the effect of some food additives (thebax and vitamin C) on the growth parameters of grass carp fingerlings. Laboratory experiments were also conducted for the cultivation of grass carp, which indicated that the best protein level in the prepared diets was 25% (Taher, 2017).…”
Section: Introductionmentioning
confidence: 99%